Cultural Intervention Model in Education Based on Local Wisdom of Kankain Karkara for the Prevention of Gender-Based Violence in Biak Numfor - Tamher, Fatmah W.; Nursida, Andi; Salehuddin, Salehuddin; Utomo, Jepri (Universitas Tanjungpura, 2025)
Gender-based violence remains a pressing issue in Biak Numfor Regency, Papua, with official data reporting dozens of cases involving women and children each year. However, these figures do not fully reflect the actual conditions, as many cases go unreported due to social stigma and a prevailing culture of silence. Within the local Biak context, the indigenous wisdom of Kankain Karkara which emphasizes sitting together, reflecting, and resolving issues through customary deliberation offers significant potential as a cultural foundation for educational interventions aimed at preventing gender-based violence. The values of solidarity, consensus, adherence to customary norms, and peace embedded in Kankain Karkara provide a strong basis for developing an educational model that fosters gender-sensitive environments. This study aims to formulate an educational model rooted in local wisdom to strengthen collective awareness and build a gender-responsive educational ecosystem. The research employed a qualitative approach with a participatory case study design. Data were collected through in-depth interviews with customary leaders, officials from DP3AKB/UPTD PPA, NGO activists, teachers, and students; participatory observations in schools and indigenous communities; as well as document analysis. Data analysis was conducted using the Miles and Huberman interactive model, comprising data reduction, display, and conclusion drawing. Model validation was carried out through focus group discussions (FGDs) involving key local stakeholders. The findings demonstrate that integrating Kankain Karkara into education can serve as an effective strategy to overcome cultural silence, reduce stigma, and enhance gender literacy among younger generations. In conclusion, education based on local wisdom is not only contextually relevant but also functions as a transformative strategy that bridges indigenous values, formal policies, and educational practices. This model has the potential to be replicated in other regions with similar cultural characteristics to promote the creation of more just and gender-equitable societies.